Assessing Financial Access in Brazil - Kumar, Anjali; Beck, Thorsten; Campos, Cristine; Chattopadhyay, Soumya (Washington, DC: World Bank, 2012)
This paper is organized as follows: Chapter 1 Introduction. Chapter 2 investigates the extent to which the supply of banking services has increased or diminished over time, and also analyzes factors underlying the spatial distribution of banking services, and the relative roles of public and private banks. Chapters 3 and 4 look at the use of financial services by urban individuals and analyze factors accounting for differentials in access-in particular the importance of regional and local differentials in access, the role of public versus private financial institutions, and the role of individual characteristics that could serve as proxies for information on creditworthiness. The final chapter summarizes the findings of this paper.